Topical 5% Dapsone Applied Twice Daily for Facial Acne Vulgaris: More Effective on Inflammatory Lesions and Quicker in Female Patients - Özkoca, Defne; Caf, Nazlı; Metin, Zuhal; Özdil, Ayşenur; İmren, Işıl Göğem; Temiz, Selami Aykut; Metin, Mahmut Sami; Durmaz, Koray; Akça, Hanife Merve; Uzunçakmak, Tuğba Kevser; Kutlubay, Zekayi (Cerrahpaşa Medical Journal, 2024)
Objective: Topical 5% dapsone is an effective alternative in the treatment of facial acne vulgaris. The aim of this study is to determine the impact of gender and age of the patient on the treatment efficacy of dapsone gel, as well as its efficacy on types of lesions. Methods: Patients with mild-to-moderate facial acne vulgaris lesions, aged between 12 and 40 years of age were included in this multicenter study. Patients received 5% dapsone gel twice daily treatment for 8 weeks. Follow-up consultations were in weeks 2 and 8. The number of inflammatory and non-inflammatory lesions and the Global Evaluation of Acne Scale (GEAS) score of the patients were noted in each visit. Results: A negative correlation was found between age and the treatment response of inflammatory lesions in week 2 (rs = −0.201; P = .008). Inflammatory lesions responded to treatment more compared to non-inflammatory lesions both on week 2 and week 8 (P-values both <.001). Female patients had a greater decline in both the number of inflammatory lesions and the total number of lesions on week 2 (P < .001 and P = .039 respectively). An at least 1 grade decline in the GEAS score was observed significantly more in the female patients on week 2 compared to male patients (P = .033). Conclusion: Topical dapsone is more effective in the treatment of inflammatory lesions than of the non-inflammatory lesions, and female patients have a quicker response. Cite this article as: Özkoca D, Caf N, Metin Z, et al. Topical 5% dapsone applied twice daily for facial acne vulgaris: More effective on inflammatory lesions and quicker in female patients. Cerrahpaşa Med J. 2024;48(1):46-49.